Opposite Effects of GSTM1 – and GSTT1 – Gene Deletion Variants on Bone Mineral Density. Issue 5 (26th May 2013) - Mlakar, Simona Jurkovic; Osredkar, Josko; Prezelj, Janez; Marc, Janja
Abstract : Oxidative stress is associated with osteoporosis. The glutathione S-transferases form the major detoxifying group of enzymes responsible for eliminating products of oxidative stress. We have therefore proposed GSTM1 and GSTT1 genes as candidates for studying the genetics of osteoporosis. The aim of the present study was to examine possible association of GSTM1 and GSTT1 gene deletion polymorphisms, alone or in combination, with bone mineral density at femoral neck (BMD_fn), lumbar spine (BMD_ls) and total hip (BMD_th) in Slovenian elderly women and men. GSTM1 and GSTT1 gene deletion polymorphisms in 712 elderly people were analyzed using the triplex PCR method for the presence of GSTM1 and GSTT1 gene segments. BMD_fn, BMD_ls and BMD_th were measured by the dual-energy X-ray absorptiometry (DEXA) method. Results were analyzed using univariate statistic model adjusted for sex, body mass index (BMI) and age. Our results showed the significant differences in BMD_th, BMD_ls and BMD_fn values ( p = 0.031, 0.017 and 0.023, respectively) in subgroups of GSTT1 gene deletion polymorphism. For GSTM1 gene deletion polymorphism borderline significant association was found with BMD_ls ( p = 0.100). Furthermore, subjects with homozygous deletion of GSTT1 gene showed higher BMD values on all measured skeletal sites and, in contrast, subjects with homozygous deletion of GSTM1 gene showed lower BMD values. Moreover, a gene-gene interaction study showed significant association of GSTM1 -null and GSTT1 -null polymorphisms with BMD_ls values ( p = 0.044). Carriers with a combination of the presence of GSTT1 gene and the homozygous absence of GSTM1 gene fragment were associated with the lower BMD values at all skeletal sites. The significant association of combination of GSTT1 gene presence and homozygous absence of GSTM1 gene with BMD was demonstrated, suggesting that it could be used, if validated in other studies, as genetic marker for low BMD.